2011
DOI: 10.12968/bjon.2011.20.9.559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient death on nursing staff: a literature review

Abstract: Background:There were 509,090 deaths recorded in England and Wales for 2008 (ONS, 2010).Of these numbers over 56% (260,000) occurred in National Health Service Hospitals, This shows the large numbers of people dying each year in hospitals. The death of a patient is an event which most if not all nursing staff will encounter during their work.This experience can elicit physical, cognitive, behavioural, spiritual and emotional responses (Parkes, 1998). Aim:The aim of this literature review is to explore how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 21 publications
7
71
0
1
Order By: Relevance
“…Research into nurses’ experiences with patient death has identified a number of themes similar to those found by this study 27. Future research could explore whether the particular finding of action versus presence is also applicable to nurses, allied health professionals and others dealing with patient death.…”
Section: Discussionsupporting
confidence: 62%
“…Research into nurses’ experiences with patient death has identified a number of themes similar to those found by this study 27. Future research could explore whether the particular finding of action versus presence is also applicable to nurses, allied health professionals and others dealing with patient death.…”
Section: Discussionsupporting
confidence: 62%
“…And also the findings are consistent with the results from hospice education with care workers participants [26,27]. Patients' death has negative effects on nurses' emotions, because their care is emotionally interactive with patients from the acute stage to terminal stage [28]. Actually, it was reported that 92.0% of nurses complain of caring for terminal patients [29].…”
Section: Effects Of the Programsupporting
confidence: 83%
“…For decades, researchers have suggested that student nurses' first experiences with patient death can have a significant influence on practice, and attitudes regarding death and dying can be firmly established by the time nurses qualify (Chen et al, 2006;Hurtig and Stewin, 1990;Khader et al, 2010). Nurses who find early encounters with death and dying very difficult can experience feelings of inadequacy, helpless, defensiveness or distress and coping mechanisms such as suppression, distancing and avoidance may be adopted (Cooper and Barnett, 2005;Kent, 2004;Terry and Carroll, 2008;Wilson and Kirshbaum, 2011). This can potentially impact on the quality of care delivered, job satisfaction, turnover and attrition.…”
Section: Introductionmentioning
confidence: 99%